Flight rescheduling, fleet rerouting and passenger reassignment for typhoon disruption events. Issue 8 (14th September 2022) - Yan, Shangyao; Chen, Yi-Chun
ABSTRACT: This study aims to develop a model to help carriers effectively and efficiently deal with flight rescheduling and passenger transport problems after a typhoon disruption event. A network flow technique is employed to construct an optimization model with the objective of minimizing the total operating costs. The model is formulated as an integer multiple network flow problem with certain side constraints, and is characterized as NP-hard. To efficiently solve realistically large problems, a heuristic algorithm is developed. Moreover, a dynamic application framework is proposed to assist decision makers in running the model and adjusting the flight schedule with the passage of time. To evaluate the model and the heuristic algorithm, a case study based on the operations of a major Taiwan airline is performed. The test results demonstrate that the model and the algorithm could be useful references in actual operations.